2002
DOI: 10.1089/08927790260472944
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Resection: A Good Alternative to Standard Loop Resection in the Management of Prostates >40 cc

Abstract: The use of a thick vapor resection loop for TURP coupled with higher generator settings as recommended for them, especially for prostates >40 cc, is beneficial, as it significantly reduces operating time, blood loss, irrigant requirement, nursing contact time, and duration of catheterization, besides providing clear vision during surgery and ease of resection. There was no reduction in efficacy or increase in complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
3
8
1
Order By: Relevance
“…In TUVRP, there is resection of tissue as in standard TURP; therefore, the outcome is as good as TURP. In 2002, Gupta et al [15] conducted a study that compared standard TURP with TUVRP in prostates more than 40 grams. The procedure is associated with better hemostasis and shorter operative time [8].…”
Section: Transurethral Vapor Resection Of the Prostatementioning
confidence: 99%
“…In TUVRP, there is resection of tissue as in standard TURP; therefore, the outcome is as good as TURP. In 2002, Gupta et al [15] conducted a study that compared standard TURP with TUVRP in prostates more than 40 grams. The procedure is associated with better hemostasis and shorter operative time [8].…”
Section: Transurethral Vapor Resection Of the Prostatementioning
confidence: 99%
“…The advantage of TUVRP includes instantaneous bulky tissue removal, with greater visibility, better hemostasis, and less bleeding [13][14][15][16] . We demonstrated that average time for postoperative irrigation was significantly reduced, including the volume of irrigant fluid, diminished admission time and early catheter removal.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials have been performed using transurethral vaporization of the prostate [7][8][9]. To the best of our knowledge, it would appear that such procedures have, in general, little advantages as regards the clinical outcome when compared with the TURP procedure.…”
Section: Discussionmentioning
confidence: 99%